A Needs Analysis of E-LKPD (Electronic Student Worksheets) in Dynamic Electricity Learning to Stimulate Critical and Creative Thinking Skills - Kharen Riz Lambar Wati; I Wayan Distrik; Viyanti (Jurnal Penelitian Pendidikan IPA, 2025)
This study investigates the need for developing electronic student worksheets (e-LKPD) for teaching dynamic electricity in junior high school science. Drawing on responses from 20 science teachers in Bandar Lampung, the research identifies key instructional challenges and teachers’ expectations for more effective digital learning tools. The findings reveal that conventional worksheets are often teacher-centered, lack interactivity, and do not adequately support the development of students’ critical and creative thinking. Teachers strongly advocate for e-LKPDs that are interactive, contextualized, visually engaging, and enriched with features such as simulations, videos, and inquiry-based tasks. They also emphasize the importance of aligning e-LKPDs with the national curriculum, students’ cognitive levels, and pedagogical strategies that promote student autonomy and collaboration. These insights point to the urgent need for e-LKPDs that are not only technologically enhanced but also pedagogically sound, capable of fostering higher-order thinking and real-world problem-solving. The study offers practical implications for instructional designers, curriculum developers, and educators seeking to improve the quality of science learning through contextual and student-centered digital resources.